Semantic-onomasiological pecularity of the lexico-phraseological field ‘anxiety’ in the Russian, Belarusian, English and German languages - Kornakova, Viktoria I. (Journal of the Belarusian State University. Philology, 2022)
The article considers the onomasiological features of the semantic field ‘anxiety’ in the Russian, Belarusian, English and German languages. Five classes of different types of motivation and idiomaticity are distinguished within the field: 1) phonetically motivated non-idiomatic names; 2) component-by-component motivated non-idiomatic names; 3) figuratively motivated idiomatic names; 4) partially (by a bound component) non-motivated and idiomatic names; 5) synchronously completely non-motivated highly idiomatic names. In all four languages, there is a tendency towards motivation of lexemes and phrasemes with the semantics of ‘anxiety’. The volume of onomasiological classes is compared both within the framework of whole semantic fields and within their lexical and phraseological sectors. There is a difference in the onomasiological structure of the lexical sectors of the semantic field ‘anxiety’ in synthetic and analytical languages. Phraseological sectors of the fields in four languages, as well as the fields themselves, are similar in onomasiological terms. The correlation between the types of meanings (cognitive vs emotional) of nominative units and their onomasiological characteristics is analysed. The studied material reveals the connection between the nominative function of a linguistic unit and its onomasiological type: conceptual meanings are expressed mainly by component-by-component motivated non-idiomatic lexemes, emotive semantics – by figuratively motivated idiomatic nominative units, mainly phrasemes.
Keywords: lexeme; phraseme; motivation; idiomaticity; analytical languages; synthetic languages; cognitive meaning; emotional meaning.